Pensamiento estratégico para la exportación de ganado bovino en pie (2020)
The purpose of the present degree work is to analyze the impact that strategic thinking would have on the export of standing cattle, to know how this whole process is carried out and all that must be taken into account in order to carry out this type of activity, inquiring about the export conditions that must be met in order to export these live animals, what their requirements are in terms of animal welfare and health, until we know how the export process is carried out in legal and administrative terms. We must understand how we can use uncertainty in our favor with good decision making, that is, how we can make sense of the actions of the past, learning from them in order to make better decisions in the present that will guide us to a more promising future, where decision processes are more effective, in order to finally obtain an export process in which an execution that manages to reduce risks takes precedence, prevent problems, ensure animal welfare in their export conditions, comply with all the legal and administrative requirements for carrying out this process.